Breaching Indigenous Law: Canadian Mining in Guatemala - Shin Imai, Ladan Mehranvar, and Jennifer Sander (My University, 2016)
This is a case study of a small Indigenous community in Guatemala that defied a powerful Canadian mining company by holding a community vote on whether to allow mining on its territory. The result of the vote—to stop mining activity on its territory—has not been honored by the Canadian mining company. The dispute is being played out against a backdrop of intimidation and violence. The study reviews the major players in the dispute—the mining company, the Guatemalan government, the World Bank and the Canadian government—and concludes that they all have a stake in the profitability of the mine. There is a clear deficiency in the checks and balances needed to ensure that the Indigenous people are dealt with fairly. Drawing on ideas from the National Roundtables on Corporate Social Responsibility (“CSR”) and the Canadian Extractive Industry in Developing Countries, the study suggests that at the present time, Canadian courts may be the only forum capable of holding the major actors accountable for their actions.